(Unpacking) father involvement in the context of childhood neurodisability research: a scoping review. Issue 1 (2nd January 2019) - Bogossian, Aline; King, Gillian; Lach, Lucyna M.; Currie, Melissa; Nicholas, David; McNeill, Ted; Saini, Michael
Abstract: Background: In the past thirty years, theoretical and empirical scholarship on father involvement has emerged and firmly established itself. Efforts to define, measure, and explore outcomes related to father involvement in the context of childhood neurodisability are evident but less well established. The purpose of this study was to systematically map empirical studies on father involvement in the context of childhood neurodisability in order to delineate the current state of research and to highlight profitable directions for future research. Methods: A rigorous scoping review method was used to select and analyze empirical studies published between the years 1988 and 2016 in order to systematically map research findings about fathers' affective, behavioral, and cognitive involvement. Results: Fifty-four ( n  = 54) studies (quantitative n  = 47 and qualitative n  = 7) met inclusion criteria associated with three levels of review. Four main trends emerged: (a) paternal "stress" is a main concept of interest; (b) comparison of mothers and fathers on affective and cognitive involvement; (c) lack of a focus on fathers' behavioral involvement, and (d) the absence of research designs that allow for examination of fathers' unique perspectives. Conclusions: Fathers are generally underrepresented in research in the context of childhood neurodisability. While there is a lack of depth in this area of research, granular analyses revealed important and unique differences about fathers' parenting experiences. Recommendations for research and practice are provided. Implications for rehabilitation: Fathers are underrepresented in the parenting in childhood neurodisability literature. Fathers who report feeling competent in parenting and connected to their child also report less parenting distress and more satisfaction in their couple relationship and family environment. Rehabilitation and allied health professionals should include fathers in parenting/family assessments. Manifestation of distress may differ among family members. Rehabilitation and allied health professionals should offer individualized care that is attuned to the needs of all family members.